2021
DOI: 10.1007/978-3-030-79382-1_9
|View full text |Cite
|
Sign up to set email alerts
|

All that Glitters Is Not Gold

Abstract: The aim of a process discovery algorithm is to construct from event data a process model that describes the underlying, real-world process well. Intuitively, the better the quality of the input event data, the better the quality of the resulting discovered model should be. However, existing process discovery algorithms do not guarantee this relationship. We demonstrate this by using a range of quality measures for both event data and discovered process models. This paper is a call to the community of IS engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…A somewhat related issue on the confidence an analyst can put in the performance of a process discovery algorithm was brought up by Van der Werf et al [37]. They observed that process discovery techniques not always discover better process models when provided with a better sample of the process behavior, i.e., a larger event log with observations of process behavior.…”
Section: Model Qualitymentioning
confidence: 99%
“…A somewhat related issue on the confidence an analyst can put in the performance of a process discovery algorithm was brought up by Van der Werf et al [37]. They observed that process discovery techniques not always discover better process models when provided with a better sample of the process behavior, i.e., a larger event log with observations of process behavior.…”
Section: Model Qualitymentioning
confidence: 99%